2015
DOI: 10.1039/c5ta01661d
|View full text |Cite
|
Sign up to set email alerts
|

Pristine and defect-containing phosphorene as promising anode materials for rechargeable Li batteries

Abstract: The pristine and defect-containing phosphorene as promising anode materials for Li-ion batteries (LIBs) have been systematically investigated by first-principles calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
91
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(95 citation statements)
references
References 49 publications
3
91
1
Order By: Relevance
“…Its structural and other properties have previously been discussed. 11,17 Due to the sp 3 hybridization, phosphorene does not form atomically flat sheets like graphene. 15 Instead, they form a puckered honeycomb-structured layers 18 (Fig.…”
Section: Phosphorene Basic Propertiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Its structural and other properties have previously been discussed. 11,17 Due to the sp 3 hybridization, phosphorene does not form atomically flat sheets like graphene. 15 Instead, they form a puckered honeycomb-structured layers 18 (Fig.…”
Section: Phosphorene Basic Propertiesmentioning
confidence: 99%
“…The key characteristics that make it so promising are high carrier mobility, strong in-plane anisotropy, particularly the anisotropy of electric conductance, 10 and highly tunable band gap, which changes with doping, functionalization, and the number of layers from~1.5 eV for a monolayer to 0.3 eV for bulk BP. 11 The on/off ratio and the carrier mobility are also layer-dependent. 12 Furthermore, compatibility of phosphorene with other 2D materials in socalled van der Waals heterostructures can offer solutions for important issues, such as surface degradation, doping, or control of surface/interface electronic structure, and can also enable novel functionalities and devices with unique or unprecedented performance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[128,[240][241][242][243][244][245][246] For Figure 11. The results showed that phosphorene is highly expected to present great opportunities for both high-performance LIBs and SIBs.…”
Section: Phosphorenementioning
confidence: 99%